The main directions and ways to improve the management of innovative development of urban infrastructure - Zhabytay, B.N.; Dosmaganbetov, N.S.; Aybasova , G.K. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the main directions and ways to improve the management of innovative development of the city and its infrastructure on the example of Astana. The main purpose of the article is effective implementation of regional investment, industrial, transport and environmental policy of innovative development of urban infrastructure, as well as identification and analysis of problems and features of innovative development of urban infrastructure through state support and development of small and mediumsized businesses. On the example of the city of Astana the statistical data of the relevant authorities on the state of these types of policy of innovative development of urban infrastructure and modern indicators of small and medium-sized businesses in the region are given. Theoretical foundations of the article the main ideas and suggestions, judgments and conclusions provided in it make a certain contribution to the theory of management of innovative development and can be used for effective management of innovative development of the city and its infrastructure. Since the theory of effective management is constantly transforming the basic content, structure and functions, methods and forms of management of innovative development of the city and its infrastructure to ensure sustainable economic growth of the city.